Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) : Review of the Effectiveness of the Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Fund's Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) program has significantly contributed to the international community's response to money laundering and the financing of terrorism. This paper reviews how the Fund's AML/CFT program has evolved during the past five years and discusses how the Fund could move forward in this area. The past five years have witnessed significant changes to the Fund's AML/CFT technical assistance program. It is now being delivered more strategically than in the past and is almost exclusively funded by external resources. Its central pillar is now the AML/CFT Topical Trust Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet